Hubungan Tingkat Kehadiran Balita di Posyandu dengan Hasil Pengukuran Antropometri Balita di Posyandu Balitaku Sayang Rw.04 Kelurahan Jangli Kecamatan Tembalang Kota Semarang - Puji Lestari; Agustin Syamsianah; Mufnaety - (Jurnal Gizi, 2012)
The low of presentation toddler’s mother to the posyandu is probably caused by some reasons, they are: mothers are too busy/cannot manage their times on housework, the less of information spreading about weighing advantage so that toddler’s mother have less or no understanding about the purpose and the advantage of weighing, the less of family support and also the poor of economic condition. Measurement of antropometri has been used most because of its more practicality, it is accurate enough, and it is easy to be done by everyone by simple practices that are common used in posyandu. The less of nutrition is not because of the lack of food but also a disease. Indirectly motive are family food endurance, children care pattern, and health services.The study which is done is explanatory research study in society nutrition field with cross sectional study approach which studies the relation of toddlers presentation to posyandu with toddler antropometri measurement result. Population which is taken in this study are toddlers who registered in “Balitaku Sayang” posyandu Rw 04, Jangli district, Tembalang subdistrict which are 160 toddlers. While samples which are taken are 62 toddlers registered to “Balitaku Sayang” Posyandu. This study uses random sampling method as the technique.The result shows that 90,30% of toddlers are not active in posyandu, antropometri of index of measurement is BB/U 80,60% good nutrition, antropometri of index of measurement is TB/U 69,40% normal. Antropometri of indeks of measurement is BB/TB 85,50% is normal.The study result showed that there is no relation between toddler’s presentation in Posyandu and the result of antropometri measurement of toddlers index of BB/U. There is a relation between toddlers presentation in Posyandu and toddler antropometri measurement of TB/U index. For last, there is no relation between toddlers presentation in posyandu and the toddlers antropometri measurement result of BB/TB index.Kata Kunci : Posyandu, Antropometri, under five years old